Les fondements de la géographie humaine - Paul Claval (Confins)
Human geography analyses space as the material support and environment of societies and insists on the way men perceive and think it. The simplified models of origins, the more subtle Vidal de la Blache’s one and the economic functionalism of New Geography are succeeded by the cultural approach: a model based on (ii) the concrete space of observed realities and (ii) the space and society instituted by (iii) human imaginaries. It allows men to structure their relations with environment, to articulate those they develop with other persons according to social rules and to bring them alive through values and intents, either those of realization or conviction ethics. Social actors implement cooperation and competition in the fields of power, wealth and prestige. This last one receives at last the consideration it deserves. The cultural approach is peculiarly illuminating in order to understand the dynamics of to-day world. The geography it explores is not only that of scholars. Everybody wears in oneself an original version of it.